Prolonged ischemia of the ileum and colon after surgical mucosectomy explains contraction and failure of "mucus free" bladder augmentation. Issue 4 (August 2022) - Urbán, Dániel; Varga, Gabriella; Érces, Dániel; Marei, Mahmoud Marei; Cervellione, Raimondo; Keene, David; Goyal, Anju; Cserni, Tamás
Summary: Introduction: Mucus production by the intestinal segment used in bladder augmentation results in long term concerns especially stones and UTI. Bladder augmentation with demucosalized intestinal flap is a potential promising approach for mucus-free bladder augmentation, however the contraction of the flap remains a major concern. Mucosectomy has been shown to result in abrupt and immediate cessation of microcirculation in the ileum. However, assessment of microcirculation shortly after mucosectomy may miss a gradual recovery of micro-circulation over a longer period of time. Previous studies have not assessed the colon response to mucosectomy. Objective: Our aim was to assess the effect of mucosectomy on the microcirculation of the colon and ileum beyond the known warm ischemia time. Study design: Ileum and colon segments were detubularised and mucosectomy was performed in (n = 8) anesthetised minipigs. Group A : sero-musculo-submucosal flaps were created with removal of the mucosa and preserving the submucosal layer Group B : sero-muscular flaps were created with the removal of submucosal-mucosal layer. The Microvascular Flow Index (MFI), the velocity of the circulating red blood cells (RBCV) was measured using Intravital Dark Field (IDF) side stream videomicroscopy (Cytoscan Braedius, The Netherlands) after mucosectomy, for up to 180 min. Results: Both the MFI and RBCV showed an abrupt reduction of microcirculation, on both surfaces of the remaining intestinal flap, in the ileum as well as in the colon. Slightly better values were seen in Group A of the colon, but even these values remain far below the preoperative (control) results. Some, tendency of recovery of the microcirculation was noted after 60–90 min, but this remained significantly lower than the preoperative control values at 180 min. Conclusion: Both the ileal and the colonic flap remains in severe ischemia after mucosectomy beyond the warm ischemia time. Discussion: This study shows that surgical mucosectomy compromises vascular integrity of the intestinal flaps used for bladder augmentation. Partial recovery which occurs within the warm ischemia time is not significant enough to avoid fibrosis therefore flap shrinkage may be inevitable with this technique. Limitation: The gastrointestinal structure of the porcine model is not the same exactly as the human gastrointestinal system. However, although not an exact match it is the closest, readily available animal model to the human gastrointestinal system.